Part-Time Employment: Future Trends in Singapore - LEE, Jean S. K. (Institutional Knowledge at Singapore Management University, 1993)
The growing shortage of workers in the labour force in Singapore is a well-recognized fact. The slowing population growth rate and the present policy on foreign workers is forcing various industries to resort to hiring part-time workers. Although the Singapore government has been encouraging employers to offer more part-time employment, the part-timers' share of the total workforce is still lagging behind that of many other countries. This paper, based on the statistics in the Reports on the Singapore Labour Force Survey and of the Singapore National Employers' Federation, aims to explain the demand for part-time workers and to analyse the potential and problems of the part-time workforce in Singapore. Some strategies are recommended to employers to increase part-time employment.